FAKTOR-FAKTOR YANG MEMPENGARUHI DIVIDEN KAS - Heriyani, Lusi; Risa, Nurma (Jurusan Akuntansi Fakultas Ekonomi Universitas Islam 45, 2015)
The purpose of this study is to give evidence that earning per share, operating cash flow, free cash flow, and lastyear cash dividen can influence current cash dividen. Sample of this study is manufacture company listed in BEI atthe year 2010 ? 2012. Data analysis used regression linear, with t-test for testing the hypothesis. The result areearning per share, operating cash flow and free ash flow can not influence the current cash dividen. But, last yearcash dividen can influence the current cash dividen.